Improvement of Methods for the Prevention of Obstetric Complications in Women with Fetus Macrosomia (Eurasian Medical Research Periodical, 2023)
Fetal macrosomia is associated with significant maternal and neonatal morbidity. In the long term, infants who are large for gestational age are more likely than other infants to be obese in childhood, adolescence and early adulthood, and are inherently at higher risk of cardiovascular and metabolic complications in adulthood. With over one billion adults in the world now overweight and more than 600 million clinically obese, preventing the vicious cycle effect of fetal macrosomia and childhood obesity is an increasingly pertinent issue. Fetal growth is determined by a complex interplay of various genetic and environmental influences. Consequently the prediction of pregnancies at risk of pathological overgrowth is difficult. Many risk factors for fetal macrosomia, such as maternal obesity and advanced maternal age, are also conversely associated with intrauterine growth restriction. Sonographic detection of fetal macrosomia is notoriously fraught with difficulties, with dozens of formulas for estimated fetal weight proposed but few with sufficient sensitivity to alter clinical practice.